Epidemiology and Molecular Characterization of Multiple Avian Influenza A/H5 Subtypes Circulating in House Crow (Corvus splendens) and Poultry in Bangladesh. (March 2022) - Islam, A.; Islam, S.; Samad, M.A.; Hossain, M.E.; Hassan, M.M.; Alexandersen, S.; Flora, M.S.; Rahman, M.Z.R.; Epstein, J.; Klaassen, M.
Abstract : Purpose: Bangladesh has faced recurrent house crow ( Corvus splendens ) mortality incidents due to highly pathogenic avian influenza (HPAI) viruses since 2011. We investigated one such event in Dhaka in 2017 to detect and molecularly characterize the avian influenza virus (AIV) in crows and poultry from nearby live bird markets (LBMs). Methods & Materials: We collected cloacal and oropharyngeal swabs from moribund and dead crows (N=163) and environmental samples from 16 neighboring LBMs (N=145). We tested all samples using specific q-PCR for influenza A (M gene) H5/H7/H9/N1/N2/N6. All H5 positive samples were inoculated into embryonated eggs for virus culture. We performed conventional RT-PCR and Sanger sequencing of the isolated viruses and used MEGAX for phylogenetic analysis. Results: We identified 3 house crow roosts that had evidence of crow morbidity and mortality and crows feeding on poultry offal and wastage in neighboring LBMs. Ninety-one percent of crows (n=149; 95% Confidence Interval (CI):86-95) were positive for A/H5 including 89.3% for H5N1 (n =118), 2.0% for H5N6 (n = 3) and 8.7% H5Nx (n = 13). Among LBMs samples, 58.3% were positive with A/H5 (n=60; 95%CI:33-49), containing 88.3% H5N1 (n=53), 3.3% H5N6 (n=2), 8.3% H5NX (n=5); 8.7% for A/H9N2 (n=9), 6.8% for A/H5N1/H9N2 (n=7) and 26.2% for A/untypable (n=27). None of the crow and LBM samples were positive for H7. Phylogenetic analysis based on HA and NA genes of H5N1 and H5N6 suggests that the virus belonging to clade 2.3.2.1a and 2.3.4.4B respectively. Conclusion: Data findings suggest that multiple subtypes of H5 including H5Nx are circulating in both crows and poultry; surprisingly co-circulation of H5 subtypes in LBMs without mortality in chickens. The virus may thus have been transmitted to crows while they were feeding on poultry waste in the LBMs. Whether the virus is non-pathogenic in chickens but pathogenic in crows or it rapidly evolved in crows to become pathogenic and because mortality is unresolved. We suggest improved LBM biosecurity measures to reduce the risk of influenza virus spillover to wild birds, which would also benefit avoiding spill-over risks to humans and Bangladesh being at the epicenter of the next pandemic.